2014
DOI: 10.1186/1471-244x-14-9
|View full text |Cite
|
Sign up to set email alerts
|

Hypomania spectrum disorder in adolescence: a 15-year follow-up of non-mood morbidity in adulthood

Abstract: BackgroundWe investigated whether adolescents with hypomania spectrum episodes have an excess risk of mental and physical morbidity in adulthood, as compared with adolescents exclusively reporting major depressive disorder (MDD) and controls without a history of adolescent mood disorders.MethodsA community sample of adolescents (N = 2 300) in the town of Uppsala, Sweden, was screened for depressive symptoms. Both participants with positive screening and matched controls (in total 631) were diagnostically inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 85 publications
1
24
0
Order By: Relevance
“…Prevalence estimates of hypomania in non-clinical samples using this format of HCL-32 also appear to be comparable with bipolar disorder prevalence in other sources (Meyer et al 2007). Clinical verification of hypomania and information on bipolar disorder diagnoses would strengthen our conclusions, but it is likely that a number of individuals with hypomania symptoms will progress to a diagnosis and these symptoms are associated with a range of adverse psychiatric outcomes (Zimmermann et al 2009; Päären et al 2014). The items in the HCL-32 do not relate to symptoms of psychosis or depression, and after additional adjustment for depression the association remained, so the relationship cannot be driven by this previously identified association (Khandaker et al 2014 a ).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Prevalence estimates of hypomania in non-clinical samples using this format of HCL-32 also appear to be comparable with bipolar disorder prevalence in other sources (Meyer et al 2007). Clinical verification of hypomania and information on bipolar disorder diagnoses would strengthen our conclusions, but it is likely that a number of individuals with hypomania symptoms will progress to a diagnosis and these symptoms are associated with a range of adverse psychiatric outcomes (Zimmermann et al 2009; Päären et al 2014). The items in the HCL-32 do not relate to symptoms of psychosis or depression, and after additional adjustment for depression the association remained, so the relationship cannot be driven by this previously identified association (Khandaker et al 2014 a ).…”
Section: Discussionmentioning
confidence: 69%
“…Combined, this body of work suggests that aberrant immune response in childhood might influence the risk of a range of major mental disorders. It is recognized that hypomanic symptoms in early adulthood are associated generally with an increased risk of Axis I disorders, and specifically with developing bipolar disorder (Zimmermann et al 2009; Päären et al 2014). The result is particularly interesting as it suggests an association of subtle changes in cytokine levels in early life with hypomanic symptoms assessed in adulthood, where previous research has found immune activation returns to normal between affective episodes in bipolar disorder (Kunz et al 2011; Stertz et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed methods of this community-based study have been published elsewhere [ 10 ],[ 14 ],[ 45 ]. Briefly, 2,300 of 2,446 (93%) 16- to 17-year-olds in a mid-sized Swedish community participated in a screening procedure aimed at identifying individuals with depressive symptoms using the Beck Depression Inventory-Child (BDI-C) [ 46 ],[ 47 ] and the Centre for Epidemiological Studies – Depression Scale for Children (CES-DC) [ 48 ]-[ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…No major differences were identified between those who participated and those who were lost to follow up. Details regarding the follow-up attrition have been published previously [ 45 ].…”
Section: Methodsmentioning
confidence: 99%